Adverse airway events in parturient compared with non-parturient patients. Is there a difference? Results from a quality management project - Heinrich, Stefan; Irouschek, Andrea; Prottengeier, Johannes; Ackermann, Andreas; Schmidt, Joachim (Journal of Obstetrics and Gynaecology Research, 2015)
The fear of airway problems often leads to prolonged attempts to obtain neuroaxial (spinal anesthesia or epidural anesthesia) anesthesia in obstetric anesthesia. The aim of this institutional quality management study was to revisit existing anesthesia care in the obstetric department, focusing on the frequency of delayed or failed neuroaxial anesthesia as well as the risk of airway problems in parturient and non-obstetric patients.The clinical records from 8 consecutive years (2005-2013) were analyzed retrospectively. Cases of cesarean delivery with general anesthesia were analyzed and compared with an age-matched group of female patients undergoing non-obstetric abdominal or gynecological surgery with rapid sequence induction. Poor laryngeal visualization (Cormack-Lehane grade III or IV) and failed intubation were recorded.The records of 6393 cesarean deliveries including 851 with general anesthesia were analyzed. In 175 cases insufficient or delayed onset of regional anesthesia led to requirement for general anesthesia. The rate of poor laryngoscopic view in parturient women undergoing cesarean delivery was 14/851, and 4/814 in the reference group (P = 0.023). Failed intubation occurred in three patients undergoing cesarean delivery (0.4%) and in one non-obstetric patient (0.1%; P = 0.339).The rate of failed intubations in patients undergoing cesarean delivery may be equivalent to non-obstetric patients. In time-challenging cesarean deliveries, delay of conversion from non-successful neuroaxial anesthesia to general anesthesia in order to avoid adverse airway events does not appear to be justified.
EVALuna2:16690

Comparative study of the McGrath™ videolaryngoscope blades and conventional laryngoscopy efficacy during mechanical chest compressions: Insights from a randomized trial with 90 anesthesiologists on objective and subjective parameters - Golditz, Tobias; Schmidt, Joachim; Birkholz, Torsten; Danzl, Anja; Moritz, Andreas; Ackermann, Andreas; Irouschek, Andrea (PLoS ONE, 2024)
Aims This study aimed to compare the efficacy and utility of the McGrath™ videolaryngoscope, using the Macintosh-like McGrath™ MAC blade and the hyperangulated McGrath™ MAC Xblade with a conventional Macintosh blade under simulated resuscitation conditions. Methods A prospective, randomized study under conditions mimicking ongoing chest compressions was conducted with 90 anesthesiologists. Intubation success rates, time-to-vocal cords, time-to-intubate, and time-to-ventilate were measured. Additionally, the study assessed the subjective ratings and the perceived workload using the ‘NASA-task-load-index’ during the procedure. Results The overall intubation success rate was device dependent 99–100%. The McGrath™ MAC and McGrath™ MAC Xblade showed faster visualization times compared to conventional blades. The MAC blade demonstrated superior performance in time-to-intubate and time-to-ventilate compared to both conventional and MAC Xblades. Despite excellent visualization, the MAC Xblade posed challenges in tube placement, reflected in a prolonged intubation time of >120 seconds in one case. Both MAC and MAC Xblade reduced potential dental injuries and interruptions to chest compressions compared to conventional laryngoscopes. User experience significantly impacted intubation times with conventional laryngoscopes, but this effect was mitigated with videolaryngoscopy. Participants reported lower stress and effort when using videolaryngoscopes, with the MAC blade rated superior in perceived time pressure. Conclusion The study supports the superiority of videolaryngoscopy with a Macintosh-like blade over conventional laryngoscopy during mechanical chest compressions, particularly for less experienced users. The McGrath™ MAC blade, in particular, offers advantages in intubation time, user-friendliness, and reduced stress. However, the MAC Xblade’s challenges during tube placement highlight the need for further clinical validation. Continued research is essential to refine guidelines and improve resuscitation outcomes.
CRIS-Team Scopus Importer:2024-09-27

Comparison of clinical outcome variables in patients with and without etomidate-facilitated anesthesia induction ahead of major cardiac surgery: a retrospective analysis - Heinrich, Stefan; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Harig, Frank; Castellanos, Ixchel (Critical Care, 2014)
It is well known that etomidate may cause adrenal insufficiency. However, the clinical relevance of adrenal suppression after a single dose of etomidate remains vague. The aim of this study was to investigate the association between the administration of a single dose of etomidate or an alternative induction regime ahead of major cardiac surgery and clinical outcome parameters associated with adrenal suppression and onset of sepsis.The anesthesia and intensive care unit (ICU) records from patients undergoing cardiac surgery over five consecutive years (2008 to 2012) were retrospectively analyzed. The focus of the analysis was on clinical parameters like mortality, ventilation hours, renal failure, and sepsis-linked serum parameters. Multivariate analysis and Cox regression were applied to derive the results.In total, 3,054 patient records were analyzed. A group of 1,775 (58%) patients received a single dose of etomidate; 1,279 (42%) patients did not receive etomidate at any time. There was no difference in distribution of age, American Society of Anesthesiologists physical score, duration of surgery, and Acute Physiology and Chronic Health Evaluation II score. Postoperative data showed no significant differences between the two groups in regard to mortality (6.8% versus 6.4%), mean of mechanical ventilation hours (21.2 versus 19.7), days in the ICU (2.6 versus 2.5), hospital days (18.7 versus 17.4), sepsis-associated parameters, Sequential Organ Failure Assessment score, and incidence of renal failure. Administration of etomidate showed no significant influence (P = 0.6) on hospital mortality in the multivariate Cox analysis.This study found no evidence for differences in key clinical outcome parameters based on anesthesia induction with or without administration of a single dose of etomidate. In consequence, etomidate might remain an acceptable option for single-dose anesthesia induction.
EVALuna2:16090

Incidence and predictors of difficult laryngoscopy in 11,219 pediatric anesthesia procedures - Heinrich, Stefan; Birkholz, Torsten; Ihmsen, Harald; Irouschek, Andrea; Ackermann, Andreas; Schmidt, Joachim (Pediatric Anesthesia, 2012)
Difficult laryngoscopy in pediatric patients undergoing anesthesia.This retrospective analysis was conducted to investigate incidence and predictors of difficult laryngoscopy in a large cohort of pediatric patients receiving general anesthesia with endotracheal intubation.Young age and craniofacial dysmorphy are predictors for the difficult pediatric airway and difficult laryngoscopy. For difficult laryngoscopy, other general predictors are not yet described.Retrospectively, from a 5-year period, data from 11.219 general anesthesia procedures in pediatric patients with endotracheal intubation using age-adapted Macintosh blades in a single center (university hospital) were analyzed statistically.The overall incidence of difficult laryngoscopy [Cormack and Lehane (CML) grade III and IV] was 1.35%. In patients younger than 1 year, the incidence of CML III or IV was significantly higher than in the older patients (4.7% vs 0.7%). ASA Physical Status III and IV, a higher Mallampati Score (III and IV) and a low BMI were all associated (P < 0.05) with difficult laryngoscopy. Patients undergoing oromaxillofacial surgery and cardiac surgery showed a significantly higher rate of CML III/IV findings.The general incidence of difficult laryngoscopy in pediatric anesthesia is lower than in adults. Our results show that the risk of difficult laryngoscopy is much higher in patients below 1 year of age, in underweight patients and in ASA III and IV patients. The underlying disease might also contribute to the risk. If the Mallampati score could be obtained, prediction of difficult laryngoscopy seems to be reliable. Our data support the existing recommendations for a specialized anesthesiological team to provide safe anesthesia for infants and neonates.
EVALuna2:16625

Increased Rate of Poor Laryngoscopic Views in Patients Scheduled for Cardiac Surgery Versus Patients Scheduled for General Surgery: A Propensity Score-Based Analysis of 21,561 Cases - Heinrich, Stefan; Ackermann, Andreas; Prottengeier, Johannes; Castellanos, Ixchel; Schmidt, Joachim; Schüttler, Jürgen (Journal of Cardiothoracic and Vascular Anesthesia, 2015)
Former analyses reported an increased rate of poor direct laryngoscopy view in cardiac surgery patients; however, these findings frequently could be attributed to confounding patient characteristics. In most of the reported cardiac surgery cohorts, the rate of well-known risk factors for poor direct laryngoscopy view such as male sex, obesity, or older age, were increased compared with the control groups. Especially in the ongoing debate on anesthesia staff qualification for cardiac interventions outside the operating room a detailed and stratified risk analysis seems necessary.Retrospective, anonymous, propensity score-based, matched-pair analysis.Single-center study in a university hospital.No active participants. Retrospective, anonymous chart analysis.The anesthesia records of patients undergoing cardiac surgery in a period of 6 consecutive years were analyzed retrospectively. The results were compared with those of a control group of patients who underwent general surgery. Poor laryngoscopic view was defined as Cormack and Lehane classification grade 3 or 4.The records of 21,561 general anesthesia procedures were reviewed for the study. The incidence of poor direct laryngoscopic views in patients scheduled for cardiac surgery was significantly increased compared with those of the general surgery cohort (7% v 4.2%). Using propensity score-based matched-pair analysis, equal subgroups were generated of each surgical department, with 2,946 patients showing identical demographic characteristics. After stratifying for demographic characteristics, the rate of poor direct laryngoscopy view remained statistically significantly higher in the cardiac surgery group (7.5% v 5.7%).Even with stratification for demographic risk factors, cardiac surgery patients showed a significantly higher rate of poor direct laryngoscopic view compared with general surgery patients. These results should be taken into account for human resource management and distribution of difficult airway equipment, especially when cardiac interventional programs are implemented in remote hospital locations.
EVALuna2:16681

Management of the Expected Difficult Airway with Planned One-Lung Ventilation: A Retrospective Analysis of 44 Cases - Irouschek, Andrea; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Trufa, Denis; Sirbu, Horia; Golditz, Tobias (Thoracic and Cardiovascular Surgeon, 2024)
Background Difficult airway management is essential in anesthesia practice. Particular challenges are posed to patients who require intraoperative one-lung ventilation. Specific guidelines for these scenarios have been lacking. The recent update of German guidelines incorporates recommendations for securing the airway in anticipated difficult airway scenarios in patients requiring one-lung ventilation. However, scientific data on this specific topic is rare. Methods A retrospective analysis was conducted on adult patients undergoing thoracic surgery with one-lung ventilation from 2016 to 2021. During these years, the standard of practice has been in line with the now published guidelines. Patients with anticipated difficult airways were identified, and airway management strategies were analyzed. Results Among 3,197 anesthetic procedures, 44 cases involved anticipated difficult airways, primarily due to prior head and neck tumor treatment. Nasal bronchoscopic awake intubation followed by oral reintubation under videolaryngoscopic inspection and the use of bronchial blockers was the standard procedure. No severe complications were recorded, and one-lung ventilation was maintained successfully in all cases. Discussion The study highlights the challenges of managing difficult airways during thoracic surgery. Recommendations align with recent guidelines, emphasizing the importance of tailored approaches. The use of single-lumen tubes with bronchial blockers appears favorable over double-lumen tubes, offering comparable ventilation quality with reduced risks. Conclusion Despite limitations, the study underscores the safety and efficacy of tailored airway management strategies during one-lung ventilation in patients with anticipated difficult airways. The presented approach offers patient safety and practicability. Further multicenter studies are warranted to validate these findings and refine clinical approaches.
CRIS-Team Scopus Importer:2024-11-29
Keywords: airway (includes related subject matter); anesthesia (includes related subject matter); practice guidelines; thoracoscopy/VATS; ventilation

Managing One-Lung Ventilation in Tracheostomized Patients: A 6-Year Retrospective Analysis - Golditz, Tobias; Schmidt, Joachim; Ackermann, Andreas; Danzl, Anja; Birkholz, Torsten; Sirbu, Horia; Irouschek, Andrea (Thoracic and Cardiovascular Surgeon, 2024)
Background To ensure safe and optimal surgical conditions in thoracic surgery, one-lung ventilation is crucial. Various techniques exist to achieve one-lung ventilation. Tracheotomized patients who require one-lung ventilation represent a unique and rare subgroup that demands specialized knowledge and skills. The very limited literature has discussed alternative methods, no randomized controlled trials have addressed this issue yet. Methods We performed a retrospective analysis of patients who underwent one-lung ventilation in the Department of Thoracic Surgery of a German University Hospital between 2016 and 2021. The study assessed patient demographics, airway management techniques, ventilation parameters, and adverse events. Results In 3,197 anesthesia procedures during the observation period, 152 patients had an existing tracheostomy, of which 56 required one-lung ventilation. Among others in 42 cases, a tracheostomy tube was combined with a bronchial blocker, and in 10 cases, a double-lumen tracheostomy tube was used. There were no severe complications. Intraoperative dislocations that required repositioning of the device occurred in six patients (13.3%) with bronchial blockers and one patient with double-lumen tracheostomy tube (10%). Conclusion The management of one-lung ventilation in tracheotomized patients presents unique challenges. While double-lumen tracheostomy tubes have specific advantages, we recommend considering their use carefully. For most tracheotomized patients, bronchial blockers in conjunction with a tracheostomy tube are used, which offers safety and practicality, irrespective of the tracheostomy's age or type. Further research and randomized controlled trials are warranted to establish best practices for one-lung ventilation in this unique patient population.
CRIS-Team Scopus Importer:2024-05-03
Keywords: airway; anesthesia; guidelines; practice; trachea; ventilation

Paediatric and adult soft tissue sarcomas with NTRK1 gene fusions: a subset of spindle cell sarcomas unified by a prominent myopericytic/haemangiopericytic pattern - Haller, Florian; Knopf, Jasmin; Ackermann, Andreas; Bieg, Matthias; Kleinheinz, Kortine; Schlesner, Matthias; Moskalev, Evgeny; Will, Rainer; Satir, Ali Abdel; Abdelmagid, Ibtihalat E.; Giedl, Josef; Carbon, Roman; et al. (Journal of Pathology, 2016)
Neoplasms with a myopericytomatous pattern represent a morphological spectrum of lesions encompassing myopericytoma of the skin and soft tissue, angioleiomyoma, myofibromatosis/infantile haemangiopericytoma and putative neoplasms reported as malignant myopericytoma. Lack of reproducible phenotypic and genetic features of malignant myopericytic neoplasms have prevented the establishment of myopericytic sarcoma as an acceptable diagnostic category. Following detection of a LMNA-NTRK1 gene fusion in an index case of paediatric haemangiopericytoma-like sarcoma by combined whole-genome and RNA sequencing, we identified three additional sarcomas harbouring NTRK1 gene fusions, termed 'spindle cell sarcoma, NOS with myo/haemangiopericytic growth pattern'. The patients were two children aged 11 months and 2 years and two adults aged 51 and 80 years. While the tumours of the adults were strikingly myopericytoma-like, but with clear-cut atypical features, the paediatric cases were more akin to infantile myofibromatosis/haemangiopericytoma. All cases contained numerous thick-walled dysplastic-like vessels with segmental or diffuse nodular myxohyaline myo-intimal proliferations of smooth muscle actin-positive cells, occasionally associated with thrombosis. Immunohistochemistry showed variable expression of smooth muscle actin and CD34, but other mesenchymal markers, including STAT6, were negative. This study showed a novel variant of myo/haemangiopericytic sarcoma with recurrent NTRK1 gene fusions. Given the recent introduction of a novel therapeutic approach targeting NTRK fusion-positive neoplasms, recognition of this rare but likely under-reported sarcoma variant is strongly encouraged.
EVALuna2:6792